Effects of dichlorvos (DDV P) on the haematological properties of wistar rats (2015)
The potential sub-chronic toxicological effects of oral administration of Dichlorvos (DDVP) on wistar rats was investigated for a period of 6 weeks. Thirty-two (32) wistar rats (equal number of both sexes) were uniformly divided into two groups while each comprised of 4 divisions with four rats each, At the end of experiment, animals were sacrificed and heamatogical test was carried out to investigate the possible toxicological effects of the oral administration of the pesticide on the rats. Results generally showed a dose-pendant response with PCV, Kb, RBC and Plan values that are significantly different from each (P<0.05) among the male rats while PCV and RBC values are significantly different from each other (P<0.05) while all other heamatological parameters in both sexes showed no significantly difference from each other at P<0.05. This result suggests that ingestion of the pesticides (Dichlorvos) may not be toxic at the doses investigated